2022
DOI: 10.1111/age.13192
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid desaturase 2 affects the milk‐production traits in Chinese Holsteins

Abstract: As a member of the fatty acid desaturase family, fatty acid desaturase 2 (FADS2) gene is a rate‐limiting enzyme in the synthesis of unsaturated fatty acids and within/near to the reported QTL regions for milk‐production traits. We previously found that FADS2 is differentially expressed during different lactations of Chinese Holstein cows, and participates in lipid metabolic processes by influencing the insulin, PI3K‐Akt, MAPK, AMPK, mTOR and PPAR signaling pathways. Therefore, we considered this gene as a cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In the study of San et al, some genes which affected intramuscular fat (IMF) deposition was significantly enriched in the ECM–receptor interaction signaling pathway ( San et al, 2021 ). In our study, the target genes of upregulated DE miRNAs were enriched in the PI3K-Akt signaling pathway, calcium signaling pathway, the AMPK signaling pathway, and MAPK signaling pathway, which are associated with fat metabolism ( Fu et al, 2022 ). In our study, forkhead boxO3 ( FoxO3 ) was enriched in the PI3K/AKT signaling pathway and AMPK signal pathway.…”
Section: Discussionmentioning
confidence: 88%
“…In the study of San et al, some genes which affected intramuscular fat (IMF) deposition was significantly enriched in the ECM–receptor interaction signaling pathway ( San et al, 2021 ). In our study, the target genes of upregulated DE miRNAs were enriched in the PI3K-Akt signaling pathway, calcium signaling pathway, the AMPK signaling pathway, and MAPK signaling pathway, which are associated with fat metabolism ( Fu et al, 2022 ). In our study, forkhead boxO3 ( FoxO3 ) was enriched in the PI3K/AKT signaling pathway and AMPK signal pathway.…”
Section: Discussionmentioning
confidence: 88%
“…As the most complex trait in dairy cow production, milk production trait is regulated by many genes and environmental factors. Some nucleotide polymorphisms may be caused by a large (Fu et al, 2022;Jia et al, 2021;Potu et al, 2022) have discussed that SNPs in milk production candidate functional genes can significantly affect milk production traits of dairy cows. In addition, by adding functional gene information of target traits with large genetic effects to expand SNP marker data, the accuracy of genome breeding value prediction can be improved (de Las et al, 2020;Ye et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many researchers try to find the key genes/loci that have significant impacts on milk production traits through candidate gene analysis, genome-wide association analysis and omics data analysis strategies ( Schennink et al, 2009 ; Canovas et al, 2013 ; Cui et al, 2014 ; Liang et al, 2017 ; Bhat et al, 2020 ). Studies have shown that the milk production traits of dairy cows can be significantly affected by SNPs in the genes ( Jiang et al, 2010 ; Dux et al, 2018 ; Han et al, 2019a ; Han et al, 2019b ; Clancey et al, 2019 ; Jia et al, 2021 ; Du et al, 2022 ; Fu et al, 2022 ; Ye et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%